A comparison of the roles of privately and state-owned oil companies in developing the Arctic shelf. Issue 1 (January 2016) - Kaznacheev, Peter; Bazaleva, Regina
The Arctic shelf is the richest region of the world by overall volumes of oil and gas resources. However, countries of the Arctic basin have progressed unequally in developing them. In this article, the authors suggest that the diverging result of these countries in many ways depends on the structure of their oil and gas sectors. This article provides a comparative analysis of privately and state-owned companies' participation in Arctic projects for those countries that are at the stage of commercial production on the Arctic shelf, namely the US, Norway and Russia. An analysis of oil companies' performance indicators allows us to conclude that private companies are more efficient at developing the region than state-owned ones.